IBM: KELOMPOK PETANI PADI - Riyanto Riyanto; Rusdi Rusdi; Indah Rakhmawati Afrida (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2017)
Specific targets in this program will be used for the public discourse on the utilization of rice straw processed into organic compost, so it may be a breakthrough in order to improve the quality of the soil and also to cost savings for farmers in order to improve the welfare of farmers' lives. Activities in this program saw puti: preparation with the socialization program for data collection and observation of farmers, dissemination and delivery of organic compost machine, machine trials, application of machines in the field and practice of organic composting of rice straw, monitoring / supervision as follow continued sustainability of the program . Results obtained from this service program is kumbangsari formation of farmer groups , technology transfer in the form of organic compost machine, farmer groups Increased understanding of the technology and paradigms of organic farming and organic compost and the end result of this activity is Organic Compost.